PREDICTIVE VALUES OF MORPHOLOGICAL CHARACTERISTICS IN RHYTHMIC GYMNASTICS - Lejla Šebić-Zuhrić,; Muhamed Tabaković,; Ivan Hmjelovjec,; Almir Atiković, (Sport Scientific And Practical Aspects, 2025)
We examined the predictive values of morphological characteristics at the rhythmic gymnastics exercises performance at the sample consisting of unselected sample of 127 female pupils of first, second and third grades of high school. We used the set of the 22 variables, indicators of morphological characteristics and predictor system representatives, as well as the set of 10 basic rhythmic gymnastics elements as the indicators of criterion system. The examinees participated in a three-month rhythmic gymnastics training programme as a part of regular sport classes. The aim of the programme was to master the basic body elements: jumps, body balance, pirouettes and rhythmic gymnastics flexibility. After the three-month programme we examined the predictive values of the morphological characteristics at the 10 rhythmic gymnastics elements performance results which represent the basic movement structures of the free composition. Regression analysis showed a relatively high multiple correlation coefficients which confirms that the morphological characteristics have a high degree of predictive values in the rhythmic gymnastics elements performance results.